Functional analysis of the biochemical activity of mammalian phosphatidylinositol 5 phosphate 4-kinase enzymes. Issue 2 (19th February 2019) - Mathre, Swarna; Reddy, K. Balasankara; Ramya, Visvanathan; Krishnan, Harini; Ghosh, Avishek; Raghu, Padinjat
Abstract : Phosphatidylinositol 5 phosphate 4-kinase (PIP4K) are enzymes that catalyse the phosphorylation of phosphatidylinositol 5-phosphate (PI5P) to generate PI(4, 5)P2 . Mammalian genomes contain three genes, PIP4K2Α, 2B and 2C and murine knockouts for these suggested important physiological roles in vivo . The proteins encoded by PIP4K2A, 2B and 2C show widely varying specific activities in vitro ; PIP4K2A is highly active and PIP4K2C 2000-times less active, and the relationship between this biochemical activity and in vivo function is unknown. By contrast, the Drosophila genome encodes a single PIP4K (dPIP4K) that shows high specific activity in vitro and loss of this enzyme results in reduced salivary gland cell size in vivo . We find that the kinase activity of dPIP4K is essential for normal salivary gland cell size in vivo . Despite their highly divergent specific activity, we find that all three mammalian PIP4K isoforms are able to enhance salivary gland cell size in the Drosophila PIP4K null mutant implying a lack of correlation between in vitro activity measurements and in vivo function. Further, the kinase activity of PIP4K2C, reported to be almost inactive in vitro, is required for in vivo function. Our findings suggest the existence of unidentified factors that regulate PIP4K enzyme activity in vivo .